ANALISIS TAX HOLIDAY DAN FUNDAMENTAL PEREKONOMIAN NEGARA TERHADAP FOREIGN DIRECT INVESTMENT (FDI) DI ASEAN-9 - Sunaryo, Ridwan Pandu; Nurhayati (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2022)
In the current era of liberalization, openness to foreign capital is an important factor affecting the economic performance of a country. Foreign Direct Investment (FDI) is an important source of capital for developing countries including ASEAN member countries. This study aims to determine the effect of taxation factors, namely tax holidays and corporate income tax rates, as well as non-tax factors, namely political stability and security, regulatory quality, domestic market size, macroeconomic stability, and labor availability on FDI flows in ASEAN. This study uses panel data regression. Research data is secondary data in the form of 2010-2019 period from 9 ASEAN member countries. The results of this study indicate that taxation factors, namely tax holidays and corporate income tax rates, have no effect on FDI flows. Meanwhile, for non-taxation factors, the quality of regulations and regulations, the size of the domestic market, and macroeconomic stability have an influence on FDI flows. Other non-tax factors, namely political stability and labor availability, have no influence on FDI flows in these countries.